Who produces cold sliced meats? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Samuel Louis Oloko Wonbo (BP 268, Kribi, Cameroon), is manager of a restaurant school and runs a restaurant too. He has established a small chicken farm with 80 chickens and a vegetable garden, where he grows bell peppers, chilli peppers, tomatoes,...